let i, k be Nat; :: thesis: for D being non empty set
for f being FinSequence of D holds f /^ (i + k) = (f /^ i) /^ k

let D be non empty set ; :: thesis: for f being FinSequence of D holds f /^ (i + k) = (f /^ i) /^ k
let f be FinSequence of D; :: thesis: f /^ (i + k) = (f /^ i) /^ k
per cases ( i + k <= len f or ( i + k > len f & i <= len f ) or ( i + k > len f & i > len f ) ) ;
suppose A1: i + k <= len f ; :: thesis: f /^ (i + k) = (f /^ i) /^ k
i <= i + k by NAT_1:11;
then A2: i <= len f by ;
then A3: len (f /^ i) = (len f) - i by RFINSEQ:def 1;
then A4: k <= len (f /^ i) by ;
A5: now :: thesis: for m being Nat st m in dom ((f /^ i) /^ k) holds
((f /^ i) /^ k) . m = f . (m + (i + k))
let m be Nat; :: thesis: ( m in dom ((f /^ i) /^ k) implies ((f /^ i) /^ k) . m = f . (m + (i + k)) )
assume A6: m in dom ((f /^ i) /^ k) ; :: thesis: ((f /^ i) /^ k) . m = f . (m + (i + k))
then A7: m + k in dom (f /^ i) by FINSEQ_5:26;
thus ((f /^ i) /^ k) . m = (f /^ i) . (m + k) by
.= f . ((m + k) + i) by
.= f . (m + (i + k)) ; :: thesis: verum
end;
len ((f /^ i) /^ k) = (len (f /^ i)) - k by
.= (len f) - (i + k) by A3 ;
hence f /^ (i + k) = (f /^ i) /^ k by ; :: thesis: verum
end;
suppose that A8: i + k > len f and
A9: i <= len f ; :: thesis: f /^ (i + k) = (f /^ i) /^ k
len (f /^ i) = (len f) - i by ;
then (len (f /^ i)) + i = len f ;
then A10: k > len (f /^ i) by ;
thus f /^ (i + k) = <*> D by
.= (f /^ i) /^ k by ; :: thesis: verum
end;
suppose that A11: i + k > len f and
A12: i > len f ; :: thesis: f /^ (i + k) = (f /^ i) /^ k
thus f /^ (i + k) = <*> D by
.= (<*> D) /^ k by Th80
.= (f /^ i) /^ k by ; :: thesis: verum
end;
end;